Clinical Utility of Cerebrospinal Fluid Cell-Free DNA as Liquid Biopsy for Leptomeningeal Metastases in ALK-Rearranged NSCLC - Zheng, Mei-Mei; Li, Yang-Si; Jiang, Ben-Yuan; Tu, Hai-Yan; Tang, Wen-Fang; Yang, Jin-Ji; Zhang, Xu-Chao; Ye, Jun-Yi; Yan, Hong-Hong; Su, Jian; Zhou, Qing; Zhong, Wen-Zhao; et al. (Journal of thoracic oncology, 2019)
Leptomeningeal metastases (LMs) indicated a poor prognosis in NSCLC. LMs were more frequent in driver gene–mutated patients, and cerebrospinal fluid (CSF) cell-free DNA has shown unique genetic profiles of LM in EGFR-mutated LM. However, studies in patients with ALK receptor tyrosine kinase gene (ALK)-rearranged NSCLC with LMs are scarce. Patients with lung cancer with ALK rearrangement were screened from September 2011 to February 2018 at our institute. CSF and paired plasma were tested by next-generation sequencing. LMs were diagnosed in 30 (10.3%) of 291 patients with ALK-rearranged lung cancer. A total of 11 paired CSF and plasma samples tested by next-generation sequencing were analyzed. Driver genes were detected in 81.8% of the CSF samples (9 of 11) and 45.5% of the plasma samples (5 of 11) (p = 0.183). The maximum allelic fractions were all higher in CSF than in plasma (p = 0.009). ALK and tumor protein p53 gene (TP53) were the two most frequently mutated genes in CSF. Gatekeeper gene ALK G1202R and C1156F mutations were identified in CSF after resistance to alectinib. Multiple copy number variants were mainly found in CSF, including in EGFR, cyclin D1 gene (CCND1), fibroblast growth factor 3 gene (FGF3), and fibroblast growth factor 4 gene (FGF4). Also found were v-myc avian myelocytomatosis viral oncogene homolog gene (MYC) copy number gains and TP53 and cyclin dependent kinase inhibitor 2A gene (CDKN2A) copy number deletions. Brigatinib seemed to be effective in controlling LM. One case showed that CSF could be used to monitor disease development of LM and longitudinally monitor tumor response. Liquid biopsy of CSF is more sensitive than liquid biopsy of plasma to detect targetable alterations, characterizing resistance mechanisms on progression and monitoring tumor response in patients with ALK-rearranged NSCLC with LM. Thus, CSF might be promising as a medium of liquid biopsy in LM.